BETWEEN THE DEVIL AND THE CROSS: RELIGION, SLAVERY, AND THE MAKING OF THE ANLO-EWE - VENKATACHALAM, MEERA (Journal of African history, 2012)
The idea that mission Christianity played a pivotal role in the creation of modern African ethnic identities has become paradigmatic. Yet, the actual cultural and social processes that facilitated the widespread reception of specific ethnic identities have been under-researched. Suggesting that historians have overemphasised the role of Christian schooling and theology in ethnic identity formation, this article examines how the Anlo people of south-eastern Ghana came, over the twentieth century, to recognise themselves as part of the larger Ewe ethnic group. Although Christian missionaries were the first to conceive of ‘Ewe’ as a broad ethnic identity, a corpus of non-Christian ritual practices pioneered by inland Ewe slave women were crucial to many Anlos' embrace of Eweness.